A balancing act: changing the referral pathway following remote consultations for dizziness during the coronavirus disease 2019 pandemic. Issue 12 (5th December 2022) - Ng, J; Wilson, B; Hey, S; Bennett, A
Abstract: Background: This paper reports our experience in managing dizzy patients remotely during the coronavirus disease 2019 pandemic, and explored its safety as an alternative to face-to-face consultations. Methods: Dizzy patients referred by their general practitioner were contacted to answer a validated questionnaire. Clinicians recorded the time needed for consultations, and the diagnosis at each of the following assessment stages: after review of the electronic general practitioner letter; following completion of the questionnaire; following the telephone consultation; and/or at follow up. Patients were telephoned no earlier than three months later to determine satisfaction with the service and symptom resolution. Electronic patient records were checked for presentation to hospital because of dizziness. Results: Seventy patients had telephone consultations. None presented to the emergency department or were admitted. The majority of consultations took 15–30 minutes. The most diagnosed condition was benign positional paroxysmal vertigo. Seventy-nine per cent of patients were satisfied with the service. The questionnaire and telephone consultations demonstrated the greatest diagnosis agreement (κ = 0.40). Conclusion: Validated questionnaire and telephone consultations are a safe alternative to face-to-face consultations. Our patient referral pathway has now changed to include elements of the questionnaire.